Metallic communication cable test methods. Electromagnetic compatibility (EMC). Transfer impedance and screening attenuation of feed-throughs and electromagnetic gaskets. Double coaxial test method Part 4-10, (3rd August 2020) - British Standards Institution,
No abstract available